FORMULATION OF RED ROSE ETHANOL EXTRACT OF MOUTHWASH (Rosa damascena Mill) AS ANTIBACTERIAL TOWARD Streptococcus mutans - Nurfitria Junita; Nielma Auliah; Wantry Diasny (Borneo Journal of Pharmascientech, 2020)
It has been conducted a research about Formulation of Red Rose Ethanol Extract of Mouthwash (Rosa damascena Mill) as Antibacterial toward Streptococcus mutans. This research aim at knowing the activity of Red Rose Ethanol Extract of Mouthwash (Rosa damascena Mill) as Antibacterial toward Streptococcus mutans. In this study, using experimental research by formulating the ethanol extract of red rose (Rosa damascena Mill) mouthwash, then tested against Streptococcus mutans bacteria using the agar diffusion method. The ethanol extract of red rose (Rosa damascena Mill) mouthwash was prepared in three concentrations, namely 1%, 3%, 5%, and control solution. The various concentrations were tested for their antibacterial activity and an evaluation of the Mouthwash by organoleptic observation, pH and cycling test. Meanwhile, the antibacterial activity test used agar diffusion method using agar well diffusion. Results of the measurement of the largest average inhibition zone at a concentration of 5% of 21.4 mm. Result showed that physical stability of mouthwash tended to stable on the low temperature storage (4°C) and had an inhibitory level in strong category in obstructing the growth of Streptococcusmutans